HUBUNGAN SPORT INJURY DAN TRAINING LOAD TERHADAP TINGKAT KEBUGARAN JASMANI MAHASISWA PENDIDIKAN JASMANI - Manalu , Nimrot; Anugerah Purba, Bayu Christo; Salsabila, Firyal; Sinaga, Josua Al-Ch; Nasution, Muhammad Reza (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the relationship between sport injury and training load on the physical fitness level of physical education students. The problem in this study is based on the still high risk of sports injuries and imbalanced training loads that can affect students' physical fitness condition. This study employed a quantitative approach with a correlational design. The research sample consisted of 30 Physical Education students who actively participated in practical sports courses and routine physical training, selected using purposive sampling technique. Data collection was carried out through the distribution of Likert scale questionnaires to measure the sport injury and training load variables, as well as physical fitness tests to measure students' physical fitness levels. The research instruments had undergone validity and reliability testing prior to use. The data analysis technique used descriptive analysis and Pearson Product Moment correlation test with the assistance of the SPSS application. The results showed that there is a negative and significant relationship between sport injury and physical fitness level with a correlation value of -0.621 and a significance value of 0.001 < 0.05. Furthermore, there is a positive and significant relationship between training load and physical fitness level with a correlation value of 0.684 and a significance value of 0.000 < 0.05. The findings indicate that proper training load management and sports injury prevention are important factors in maintaining and improving the physical fitness level of physical education students.